Oxytocin attenuates microglial activation and restores social and non-social memory in APP/PS1 Alzheimer model mice - Maria Clara Selles; Juliana T.S. Fortuna; Yasmin P.R. de Faria; Luciana Domett Siqueira; Ricardo Lima-Filho; Beatriz M. Longo; Robert C. Froemke; Moses V. Chao; Sergio T. Ferreira (iScience, 2023)
Summary: Alzheimer’s disease (AD) is characterized by neurodegeneration, memory loss, and social withdrawal. Brain inflammation has emerged as a key pathogenic mechanism in AD. We hypothesized that oxytocin, a pro-social hypothalamic neuropeptide with anti-inflammatory properties, could have therapeutic actions in AD. Here, we investigated oxytocin expression in experimental models of AD, and evaluated the therapeutic potential of treatment with oxytocin. Amyloid-β peptide oligomers (AβOs) reduced oxytocin expression in vitro and in vivo, and treatment with oxytocin prevented microglial activation induced by AβOs in purified microglial cultures. Treatment of aged APP/PS1 mice, a mouse model of AD, with intranasal oxytocin attenuated microglial activation and favored deposition of Aβ in dense core plaques, a potentially neuroprotective mechanism. Remarkably, treatment with oxytocin alleviated social and non-social memory impairments in aged APP/PS1 mice. Our findings point to oxytocin as a potential therapeutic target to reduce brain inflammation and correct memory deficits in AD.